SERVICE DELIVERY PROCESS AND CUSTOMER RETENTION OF AIRLINES IN RIVERS STATE - Nzenwa, Charles; Eke, Haniel O. (Ph.D); Prof. Emeka J. Okereke (American Journals, 2024)
This study conducted an empirical investigation into the impact of the service delivery method on customer retention for airlines in Rivers State. The study utilised primary data collected through the administration of questionnaires. The study encompassed all twenty-four (24) airlines that operate in Rivers State. Due to the relatively limited number of airlines, the whole population was included in the study. The study utilised the Pearson Product Moment Correlation Coefficient to examine the link between the dependent and independent variables. The analysis revealed a strong and positive correlation between self-service technology and customer retention, leading to improvements in customer satisfaction and commitment. Similarly, service process blueprinting also showed a significant and positive relationship with customer retention, resulting in enhanced customer satisfaction and commitment. The study determined that the process of delivering services has a substantial impact on client retention. Hence, it is advisable for airlines to ensure that their self-service technologies are readily available and user-friendly. Additionally, airlines should be cognizant of how their consumers acquire information about their service offerings in order to properly manage external communications for the company.
Keywords: Service delivery process, Customer Retention, Self-Service Technology, Service Process Blueprinting, Customer Satisfaction, Customer Commitment